Dampak Internet terhadap Pola Interaksi Masyarakat di Desa Tawangharjo - Istikomah Istikomah; Iva Khoiril Mala (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This study aims to reveal the impact of the internet on community interaction patterns in Tawangharjo Village through a qualitative approach. Qualitative research methods are used to deeply understand how the internet has affected social interaction, communication, and relationships between individuals in the village context. Data were collected through in-depth interviews, participatory observation, and content analysis of various online information sources relevant to the village community. The findings show that the internet has had a significant impact in expanding access to information, changing communication patterns, influencing the way people establish social relationships, and posing new challenges related to data privacy and security. The implications of these findings highlight the importance of improving digital literacy and awareness of the risks and benefits of the internet in the context of rural communities. This research contributes to further understanding of the role of the internet in social transformation in rural areas.